If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x-8=-7x
We move all terms to the left:
9x-8-(-7x)=0
We get rid of parentheses
9x+7x-8=0
We add all the numbers together, and all the variables
16x-8=0
We move all terms containing x to the left, all other terms to the right
16x=8
x=8/16
x=1/2
| 3y+223=5 | | 5(2-3n=12-15n+8 | | 4(5n+1)=10n+4 | | -2x-3=-4x+11 | | -55.2=12.4+2x | | 12r-7r-1=19 | | 3y+22=5 | | 15x+9=117 | | v+(-20)=-14 | | 4(0.4-4x)=0.6(-5x-6) | | -107-3x=109+6x | | x3=22. | | -11n+5=9n-35 | | 12r-7r1=19 | | m-4m=3/2-5/2m | | 8.50+1.25x=40 | | 9(x+3)=6x-3 | | v+16=23 | | 8k+12=10k-8 | | 15(n+8)=795 | | 83=(3x+2) | | 5y+43=-2(1-7y) | | 819=21(z+22) | | 27-2x=2x+3-12 | | -11+5x=24 | | 6+r=44 | | 4(x+1)+1=13 | | 226=36+19x | | 12.4(x-4.7)=-218.24 | | 4(x-4)-2(3+2x)=-22 | | –13p+19p+–5=–11 | | 6x-1=61 |